Cost Analysis Of Tools Production For Shaft Fabrication Process Using Cam - Achmad Nur Khaeri (Peneliti.net, 2021)
Based on the PO from the customer, namely the manufacture of shafts using SS 316 material, so that the estimated price calculation for the shaft fabrication process is carried out. In order to complete the work, a design/drawing shaft is made according to the acceptance criteria from the customer by the engineering team. To find out the estimated cost of the fabrication process, it is necessary to calculate the fabrication cost. The method used is a tool path simulation using CAM ESPRIT 2017. The simulation process in the CAM ESPRIT 2017 application aims to determine the estimated time required for the shaft fabrication process. The machining parameters used are Sandvik tool and standard tool. After obtaining the simulation time, it can be calculated to estimate the required cost. To determine the number and cost of the required tool, the calculation of the tool life between the Sandvik tool and the standard tool is carried out.